A relação entre inflação e índices de preços ao produtor agropecuário: Uma análise por meio de séries temporais para os extremos de faixas de renda - Nogueira, João Pedro Ferreira (Universidade Federal de São Carlos, 2024)
Motivated by the central position that agriculture has in Brazil's economy, as well as by the growth, especially in the post-pandemic period, of food insecurity among lower-income Brazilians, which has, at least in part, its origin in the inflationary dynamics of food, the This objective study analyzes the impact that agricultural producer prices for three types of goods (grains, livestock products and fruit and vegetables) have on inflation for very low-income and high-income Brazilians. To this end, a model was created for each social group evaluated, inspired by the New-Keynesian Phillips curve, whose orders were made using Autoregressive Vectors with Error Correction. As a result, it was possible to demonstrate that the price for agricultural producers has a stronger impact on inflation for the poorest at the expense of inflation for the richest, at least in the period analyzed, which runs from January 2007 to March 2024.
The relationship between inflation and agricultural producer price indexes: An analysis using time series for the extremes of income ranges
Keywords: Inflação; Preços; Agropecuária; Inflation; Prices; Agriculture; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA AGRARIA